2023
DOI: 10.1002/ila2.23
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of six serum tumor markers for the diagnosis of lung cancer

Yongchang Yang,
Shuai Chang,
Na Wang
et al.

Abstract: BackgroundWith the increasing prevalence of lung cancer, it has become imperative to identify reliable biomarkers that can aid in early detection and prognosis assessment. Therefore, we sought to investigate the potential utility of six serum tumor markers as diagnostic and prognostic tools for lung cancer patients. By analyzing a large cohort of patients with different stages and subtypes of lung cancer, we hoped to shed light on the predictive value and accuracy of each marker individually, as well as their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…They found that serum progastrin-releasing peptide (ProGRP) and neuron-specific enolase (NSE) were sensitive for small cell carcinomas, whereas carcinoembryonic antigen and NSE were helpful in diagnosis of adenocarcinomas and squamous cell carcinomas. Combined use of these biomarkers may markedly improve the sensitivity of diagnosis [18]. von Hofe E et al reviewed a number of clinical trials regarding chimeric antigen receptor T cell therapy for solid tumors.…”
mentioning
confidence: 99%
“…They found that serum progastrin-releasing peptide (ProGRP) and neuron-specific enolase (NSE) were sensitive for small cell carcinomas, whereas carcinoembryonic antigen and NSE were helpful in diagnosis of adenocarcinomas and squamous cell carcinomas. Combined use of these biomarkers may markedly improve the sensitivity of diagnosis [18]. von Hofe E et al reviewed a number of clinical trials regarding chimeric antigen receptor T cell therapy for solid tumors.…”
mentioning
confidence: 99%
“…With the advancement of automation technologies, the integration of automated processing equipment into the pre-treatment steps may potentially address the drawbacks of this cRMP. Additionally, considering the absence of recognized RMPs for the determination of serum tumor markers, our next endeavor involves the application of LC-MS/MS to develop intelligent, integrated solutions for quantifying serum tumor markers [29,30].…”
mentioning
confidence: 99%